On ghosts and mirrors: A contribution on studying anthropology of difference - Bošković Aleksandar (Sociologija, 2009)
Starting from the premise that contemporary social sciences are involved in producing and chasing ghosts, the paper presents several key debates in contemporary social and cultural anthropology. One of them is the issue of colonialism, and the other one is the uneasy relationship between feminism and anthropology. Taking the paradigm of Strathern's 'partial connections,' it is claimed that the only way to increase our understanding of the world we live in, is accepting its complexities and ambiguities, and understanding contexts and concrete situations they arise from.